Department Budgeting and Resources - Don Chu; Kimihko Nomura (Academic Chairpersons Conference Proceedings, 2017)
Departments are faced with reduced appropriations and increased demands on their budgets. We will look at the three keys to respond to this fiscal environment and position your department for a brighter future: budget basics, management aimed at productivity and strategic investment, and increasing resource flow.
Keywords: budget; appropriations; fiscal management; productivity; investment